2017
DOI: 10.1016/j.str.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Highly Dynamic Nature of ERdj5 Is Key to Efficient Elimination of Aberrant Protein Oligomers through ER-Associated Degradation

Abstract: ERdj5, composed of an N-terminal J domain followed by six thioredoxin-like domains, is the largest protein disulfide isomerase family member and functions as an ER-localized disulfide reductase that enhances ER-associated degradation (ERAD). Our previous studies indicated that ERdj5 comprises two regions, the N- and C-terminal clusters, separated by a linker loop and with distinct functional roles in ERAD. We here present a new crystal structure of ERdj5 with a largely different cluster arrangement relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…This structure also revealed a binding site for EDEM, a component of the ERAD machinery for glycosylated proteins, allowing ERdj5 to provide a physical lumenal link between ER quality control of BiP clients that are often unglycosylated and lectin clients. A second ERdj5 crystallization attempt produced a different three-dimensional arrangement of the Nand C-terminal clusters (73). This suggested more flexibility in the structure than had been anticipated, and single molecule studies revealed rapid movement between the two clusters.…”
Section: Erdj5/dnajc10mentioning
confidence: 90%
See 1 more Smart Citation
“…This structure also revealed a binding site for EDEM, a component of the ERAD machinery for glycosylated proteins, allowing ERdj5 to provide a physical lumenal link between ER quality control of BiP clients that are often unglycosylated and lectin clients. A second ERdj5 crystallization attempt produced a different three-dimensional arrangement of the Nand C-terminal clusters (73). This suggested more flexibility in the structure than had been anticipated, and single molecule studies revealed rapid movement between the two clusters.…”
Section: Erdj5/dnajc10mentioning
confidence: 90%
“…In addition to possessing an N-terminal J domain, ERdj5 has six thioredoxin (Trx) domains, two of which are enzymatically inactive (Trx-like), and an ER retention sequence. Structural data show that the Trx domains are arranged in two clusters (72,73). Each cluster possesses two Trx domains, but the N-terminal cluster also has the two catalytically inactive domains.…”
Section: Erdj5/dnajc10mentioning
confidence: 99%
“…Mutational inactivation of the two most reducing thioredoxin domains in ERdj5 was subsequently shown to strongly influence the ERAD-enhancing activity of ERdj5 [18] . The efficiency of ERdj5 in catalyzing reduction-mediated ERAD has recently been shown to rely not only on the redox activity of the protein but also on its conformational plasticity [46] .…”
Section: Is Disulfide Bond Reduction Required For Er-associated Degramentioning
confidence: 99%
“…In the mammalian ER, the reactions are catalyzed by a variety of oxidoreductases which encompass more than 20 members of the protein disulfide isomerase (PDI) family (1)(2)(3)(4)(5) and more than five PDI oxidases including ER oxidoreductin-1α (Ero1α) (6-9) and peroxiredoxin-4 (Prx4) (10)(11)(12). Some PDI family enzymes also engage in disulfide bond reduction to promote protein folding (13), the ER-associated degradation of misfolded proteins (14)(15)(16), or the ER-to-cytosol retrograde translocation of a bacterial cholera toxin and non-enveloped viruses (17)(18)(19). PDI family members typically possess thioredoxin (Trx)-like domains with a CXXC motif at the redox-active site, thereby exerting thiol-disulfide exchange reactions with substrate proteins (1,3).…”
Section: Introductionmentioning
confidence: 99%